Hakekat Pendidikan Pancasila Bagi Generasi Milenial - Fransisca Jallie Pattiruhu (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
In the era of technological and information development that is all sophisticated and modern, let's call it the era of industry 4.0 which is currently taking place and will also lead to the era of society 5.0, of course, making the use of the internet and technology a primary need. It cannot be denied that there are positive and negative impacts from the use of the internet and technology, moving from the negative impact that has started to make people behave individually. Lack of care and intolerance among others, the main purpose of this paper is to analyse the concept of Pancasila education as a national character education in the midst of the current era. The research in this paper uses qualitative research methods, with descriptive analytical research type, with data collection techniques using literature review. The results of this study indicate that Pancasila education as a national character education is certainly a character formation starting from the practice of Pancasila values ​​for the millennial generation in all aspects of social, national and state life. This can certainly be done well if the strengthening of the cultivation of Pancasila values ​​is carried out both in the family environment and in the world of education or even introductory socializations that can be carried out so that the millennial generation does not lose direction, it can actually better understand the values ​​of Pancasila itself.